PENGARUH GAYA HIDUP, FITUR PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN MASYARAKAT MENGGUNAKAN JEJARING SOSIAL TWITTER DI SURABAYA SELATAN - ILHAM P, DWI (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Progress of the social media world lately be judged so rapidly in world wide. This led to growth in the number of users of social increased sharply each year. Similarly, experienced social media called twitter. As a new player in the world of social media, twitter users were experiencing very rapid growth. Because of it, makes it very interesting to study twitter. This study tries to link the decision of using on the twitte rusers are in South Surabaya specifically on Bungkul Park, Unesa Ketintang, and Researchers neighborhood with lifestyle variables, product features, and brand image. The population of this study is twitter users in the region south of Surabaya specifically on Bungkul Park, Unesa Ketintang, and Researchers neighborhood. And the sample used was 100 samples. In this study data collection using questionnaires and library research techniques.For data analysis techniques using multiple linear regression analysis, f-test and t-test. The results of this research note that lifestyle, product features, and brand image simultaneously or partially affect the twitter usage decision. Keywords: lifestyle, product features, brand image, use decisions